Occurrence of iodinated X-ray contrast media in indirect potable reuse systems - Busetti, Francesco; Linge, Kathryn; Rodriguez, C.; Heitz, Anna (Taylor and Francis, 2010)
A lack of knowledge of the health and environmental risks associated with chemicals of concern (COCs) and also of their removal by advanced treatment processes, such as micro-filtration (MF) and reverse osmosis (RO), have been major barriers preventing establishment of large water recycling schemes. As part of a larger project monitoring over 300 COCs, iodinated x-ray contrast media compounds (ICM) were analysed in treated secondary wastewater intended for drinking purposes. ICM are the most widely administered intravascular pharmaceuticals and are known to persist in the aquatic environment. A direct injection liquid chromatography tandem mass spectrometry (DI-LC-MS/MS) method was used to monitor secondary treated wastewater from three major wastewater treatment plants in Perth, Western Australia. In addition, tertiary water treated with MF and RO was analysed from a pilot plant that has been built as a first step in trialling the aquifer recharge. Results collected during 2007 demonstrate that MF/RO treatment is capable of removing ICM to below the analytical limits of detection, with average RO rejection calculated to be greater than 92%. A screening health risk assessment indicated negligible human risk at the concentrations observed in wastewater.